BUDAYA ORGANISASI DI BADAN KEPEGAWAIAN DAERAH KOTA PADANG - PUTRI WARTI SARI AKMAL (Jurnal Bahana Manajemen Pendidikan, 2016)
The goal of this research are to know the information about organizational culture in Local Employment Agency The City of Padang. The population is 49 employee people and all of them make sampel. The instrument of this research is question with Likert scale models that had tasted for validity and realiability. Data analyzed using mean score. The result of this research are the organizational culture in Local Employment Agency The City of Padang is enough category.